(untitled) (Materiali di Estetica. Terza serie, 2020)
The study offers a detailed examination of all the considerations that Leonardo dedicated to the Moon to which he wanted to dedicate a treatise, De coelo et mundo using astronomy, geology and cosmology. While sharing the Ptolemaic theory, Leonardo carried out studies on shadows, light and reflections to outline a scientific explanation. The drawing is thus also used in this case as a tool of scientific investigation that illustrates the relationships that are established between light and shadows to better investigate the physical nature of the Moon.